Microbioassay of Permethrin and Cypermethrin on Gram - Yadav, C L; Yadav, H C.L (Annals of Arid Zone, 2016)
The residues of synthetic pyrethroids such as cypermethrin 0,005% and permethrin 0.005% on gram (Cicer arietillum L.) were determined by residue film microbioassay method using one day old vinegar flies. Drosophila melallogaster Meig. The initial deposits of 1.94 and 1.35 ppm of permethrin and 1.95 and 1.79 ppm of cypermethrin were obtained on leaves and pods of gram immediately after spraying respectively. The lesidues of cypermethrin and permethrin were found to persist for 21 days on gram leaves and pods. but the residues reached below tolerance limit of 0.5 ppm in 7 days on gram leaves and in 5 days on gram pods, indicating a waiting period of 5-7 days before consumption of leaves and pods for vegetable purpose. No residue on pods and in grains at harvest was detected.